The Oxford handbook of social networks - Light, Ryan ca. 20./21. Jh; Moody, James ca. 20./21. Jh (Oxford handbooks online, 2020)
While some social scientists may argue that we have always been networked, the increased visibility of networks today across economic, political, and social domains can hardly be disputed. Social networks fundamentally shape our lives and social network analysis has become a vibrant, interdisciplinary field of research. In this handbook, Ryan Light and James Moody have gathered 40 leading scholars in sociology, archaeology, economics, statistics, and information science, among others, to provide an overview of the theory, methods, and contributions in the field of social networks. Each of the chapters moves through the basics of social network analysis aimed at those seeking an introduction to advanced and novel approaches to modeling social networks statistically